Ta’limda til va kommunikatsiya madaniyati: ko‘p tillilikda psixologik va pedagogik to‘siqlarni texnologiyalar orqali bartaraf etish (Multidisciplinary Journal of Science and Technology, 2025)
This article is dedicated to analyzing the significance of multilingualism in shaping linguistic and communication culture in education, as well as the psychological and pedagogical barriers encountered in this process. The article examines psychological challenges such as lack of motivation, fear, and insecurity faced by students when learning a new language, as well as pedagogical issues like teachers’ qualifications and the limited availability of adaptive teaching materials. It suggests ways to address these challenges through modern technologies.